Vaginal fractional carbon laser: minimally invasive means of restoring the vaginal mucosa - E Gaspar; G Eddemo; H Brandy (IP Berlin A.V., 2013)
Introduction. This article confirms that the use of the fractional carbon dioxide laser in combination with topical application of plasma with a high content of platelets (PRP) on the vaginal mucosa with minimal or mild symptoms of atrophy, as well as in combination with strengthening exercises for the pelvic floor muscles via perineometer improves the condition of all three vaginal layers, including sizeable reduction of discomfort during sexual intercourse. Materials and methods. The study was conducted on two groups: observation group and control group with the main complaints about vaginal dryness, and dyspareunia. The first group went through such PRP methods as therapy, carbon dioxide laser, and exercises to strengthen the pelvic floor muscles, whereas for patients in the control group only PRP and exercises to strengthen the pelvic floor muscles were implemented. For the survey, we used a special vaginal scanner with laser light scattering, which was specially adapted for vaginal examinations. The results in both groups were analyzed using sexological questionnaire and vaginal biopsy tissues. Results. In the observation group compared with the control group, the majority of patients showed a significant improvement in histology of the vaginal mucosa and reduced discomfort during sexual intercourse. Conclusion. The topical vaginal fractional carbon laser use, together with PRP and strengthening exercises for the pelvic floor in women with vaginal tissues atrophy symptoms, the positive effects on all three vagina layers were observed, whereas the estrogen guarantees only the epithelium condition improvements. Also a significant reduction of discomfort during sexual intercourse was observed. However, more detailed information may be required in order to clarify the procedure implementation.